The Plan S Rights Retention Strategy: Are we witnessing the end of embargo periods? - De-Castro, Pablo (Anuario ThinkEPI, 2022)
The proposal made in September 2018 by cOAlition S to progress towards full immediate open access (OA) by signing transformative agreements with publishers was received with understandable skepticism by some relevant actors in countries with lower OA implementation and lower economic resources to address this transition. This text argues that these so-called transformative agreements are bound to be most efficient where green OA is already consolidated and explores the viability of the new Rights Retention Strategy as a corollary of such a strategy.
Keywords: Open access; Plan S; Green route; Rights Retention Strategy; Transformative agreements; Scholarly communications